Time allocation and diving behaviour of harbour porpoises (Phocoena phocoena) in Danish and adjacent waters - Teilmann, Jonas; Larsen, Finn; Desportes, Genevieve (J. Cetacean Res. Manage., 2023)
To gain insight into the time allocation and diving behaviour of harbour porpoises in Danish and adjacent waters, satellite linked dive recorders were mounted on 14 harbour porpoises. The animals were incidentally caught alive by fishermen using pound nets during 1997- 99 in the Danish Belt seas. Information on diving behaviour was collected from April to November. Contact with individual porpoises remained for up to 130 days. The average number of dives per hour was 29 during April-August and 43 during October-November. Daily maximum dive depth corresponds to the depth of the Belt seas and Kattegat where depth generally does not exceed 50m. Maximum dive depth recorded was 132m from animals moving north into Skagerrak. Dives were frequently recorded in the category 10-15min, but could potentially be an artefact of the sampling regime. The diurnal pattern shows that harbour porpoises dive continuously both day and night, but with peak activity during daylight hours. On average they spent 55% of their time in the upper 2m during April-August. These values have implications for aerial abundance surveys when correcting for animals not visible. A mature female and its approximately 10 months old calf were both tagged and swam together for 43 days until contact was lost. The calf made more frequent but shorter dives than the mature female. The number of dives per hour decreased, while the dive depth and duration increased for both animals from May to June, suggesting a change in feeding behaviour. It is not known whether the female and calf synchronised their dives, but the diurnal dive pattern shows a correlated dive rhythm in May, but not in June. This change in mother-calf behaviour suggests that the calf foraged more independently, corresponding to the time of year when porpoise calves leave their mother.